Importance of Lipid Composition in the Membrane Dynamics of Urothelial Umbrella Cells - Grasso, Ernesto Javier (2014)
The studies on membrane dynamics in urinary bladder umbrella cells were focused on proteins as important factors for maintaining the permeability barrier and their role as pathways modulators for the discoidal/fusiform endocytic vesicles which is one of the main features of the umbrella cells. However, our workgroup has dedicated to the study of lipid membrane composition and its biological impact in the urothelium. We first studied the lipid membrane composition of rat urothelium modified my dietary treatments differentiated in their fatty acid composition. Changes of lipid composition were related to the asymmetric unit membrane organization and permeability. Finally, we observed that the lipid composition was critically related to the intracellular pathways of discoidal/fusiform endocytic vesicles and their content. The purpose of this communication is to summarize the importance of lipids in the membrane organization and permeability of the apical plasma membrane and endocytic vesicles of umbrella cells.